Incidence, progression and sequence of development of radiographic knee osteoarthritis in a symptomatic population. Issue 11 (2nd August 2011) - Duncan, R; Peat, G; Thomas, E; Hay, E M; Croft, P
Abstract : Objectives: Symptomatic knee osteoarthritis (OA) is a common disabling condition. Attention has tended to focus on the tibiofemoral joint (TFJ). However, there is evidence that the patellofemoral joint (PFJ) is involved in many cases, but its place in the sequence of development and progression of knee OA is unclear. This study estimates the cumulative incidence, progression and inter-relationship of radiographic changes of OA in the TFJ and the PFJ in symptomatic adults. Methods: A population-based observational cohort of 414 adults aged ≥50 years with knee pain who had knee x-rays (weight-bearing posteroanterior semiflexed, skyline and lateral views) in 2002–3 and again in 2005–6 (mean interval 36.7 months) was studied. The outcome measure was the development of incident or progressive radiographic OA. Results: The 3-year cumulative incidences of patellofemoral joint osteoarthritis (PFJOA) and tibiofemoral joint osteoarthritis (TFJOA) were 28.8% and 21.7%, respectively. Corresponding estimates of 3-year cumulative progression were 18.9% and 25.3%. PFJOA at baseline was common and increased the risk of incident TFJOA (adjusted OR 2.2, 95% CI 1.1 to 4.1) but less clearly progression of TFJOA (adjusted OR 1.7, 95% CI 0.3 to 9.0). TFJOA at baseline increased the risk of PFJOA incidence and progression (adjusted OR 3.1, 95% CI 1.2 to 8.4 and OR 4.5, 95% CI 1.8 to 11.2, respectively). Conclusions: These results suggest a common sequence in the development of radiographic knee OA in symptomatic adults beginning in the PFJ, with subsequent addition and progression of TFJOA. It is proposed that isolated symptomatic PFJOA may be one marker for the future development of TFJOA and a target for the early management of knee OA.